2023
DOI: 10.1111/wvn.12669
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of mind‐body exercise for depression in breast cancer survivors: A systematic review and network meta‐analysis

Abstract: BackgroundAs pharmacotherapy often leads to adverse reactions, mind–body exercise (MBE) treatments have become a more popular option for treating depression in people living with breast cancer (BC). However, the most effective type of MBE treatment for this population remains unclear.AimsThe aim of this systematic review and network meta‐analysis (NMA) was to compare the efficacy of the different MBE modes for depression in people with BC.MethodsA systematic search for randomized controlled trials (RCTs) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 72 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Geng et al compared the effects of several mind–body exercises on depression among breast cancer survivors (another hotspot identified in this study) using the network meta-analysis. They reported that yoga was more effective than Baduanjin, Pilates, dance, and Qigong ( 68 ). There are also several systematic reviews and meta-analyses on acupuncture, indicating that acupuncture might have some benefits in ameliorating depression, either being used alone or being used in combination with conventional treatments ( 69–71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Geng et al compared the effects of several mind–body exercises on depression among breast cancer survivors (another hotspot identified in this study) using the network meta-analysis. They reported that yoga was more effective than Baduanjin, Pilates, dance, and Qigong ( 68 ). There are also several systematic reviews and meta-analyses on acupuncture, indicating that acupuncture might have some benefits in ameliorating depression, either being used alone or being used in combination with conventional treatments ( 69–71 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there are some review articles that have summarized the potential beneficial effects of exercise on quality of life, depression, cancer-related cognitive impairment, functionality status, chronic pain, cancer-related fatigue, radiotherapy-related dysphagia, psycho-emotional status, cancer cachexia, sarcopenia, chemotherapy toxicity, bone health, and sleep disturbances [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. However, only a few outdated review articles have focused on the anti-cancer molecular mechanisms of exercise.…”
Section: Introductionmentioning
confidence: 99%